Requirement and use efficiency of nitrogen in transplanted Aman rice at Ganges tidal water flooded coastal ecosystem - Pranto, Samsunnahar; Haque, Mohammad Asadul; Hoque, Md Fazlul (Journal of Bangladesh Academy of Sciences, 2023)
Transplanted (T) Aman rice covers most of the arable land in the south coastal region of Bangladesh, where nitrogen fertilizer requirement in the Ganges tidal water flooded ecosystem yet not determined. The on-farm experiment was conducted at Dumki Upazila, Patuakhali district of Bangladesh, during T. Aman rice season 2020. The three replicated randomized complete block design was used in the experiment. There were eight treatments with different rates of nitrogen, e.g., control (no nitrogen fertilizer), 18, 36, 54, 72, 90, 108, and 126 kg N ha-1, which was equivalent to 0, 20, 40, 60, 80, 100, 120 and 140% of the current recommended rate, respectively. The test variety of rice was BR23. An increase in nitrogen rates progressively increased the grain yield of rice. The highest yield of 5.04 t ha-1 was found in 54 kg N ha-1 rate. However, using a quadratic equation, the most optimum rate was 75 kg N ha-1, 17% lower than the current recommendation. Nitrogen amendment could increase T. Aman rice grain yield by only 35% over control under tidal water flooded conditions. The agronomic efficiency, recovery efficiency, and physiological efficiency of nitrogen were higher in lower rates of N and gradually decreased with the increase of the rate of N application. The present study recommends 75 kg N ha-1 for cultivating T. Aman rice (BR23) in tidal water flooded the south coastal ecosystem of Bangladesh. J. Bangladesh Acad. Sci. 47(2); 169-180: December 2023